The use of force in international law : a case-based approach - Corten, Olivier; Hofer, Alexandra , 1990-; Ruys, Tom (Oxford University Press, 2018)
Since the adoption of the UN Charter in 1945, the use of cross-border force has been frequent. This volume invites a range of experts to examine over sixty conflicts, from military interventions to targeted killings and hostage rescue operations, and to ask how powerful precedent can be in determining hostile encounters in international law.-- Source other than Library of Congress